Some Considerations in the Translation of African Drama - Che Suh, Joseph (Meta, 2002)
AbstractThis paper examines the types of African drama South of the Sahara. It illustrates and underscores the fact that each of the numerous sub-categories found in that part of the continent has its own distinctive characteristics which the translator must actively identify and map onto the target text.